2018
DOI: 10.1016/j.jss.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of preoperative abdominal Aortic balloon occlusion in placenta increta and/or percreta

Abstract: Application of preoperative transfemoral abdominal aorta balloon occlusion during cesarean section is a safe and effective strategy for patients with placenta increta and/or percreta. It could reduce intraoperative blood loss and enhance the possibility of uterus preservation and ensure the safety of life from severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Although this technology has been applied clinically for approximately 20 years, no consensus or data are available regarding the safe dose for the foetus, and further research and statistics are needed. Sun et al [49] recommended a dose of 4.2 ± 1.9 mGy. To minimise radiation exposure, experienced interventional doctors should quickly insert the balloon into the internal iliac artery.…”
Section: Discussionmentioning
confidence: 99%
“…Although this technology has been applied clinically for approximately 20 years, no consensus or data are available regarding the safe dose for the foetus, and further research and statistics are needed. Sun et al [49] recommended a dose of 4.2 ± 1.9 mGy. To minimise radiation exposure, experienced interventional doctors should quickly insert the balloon into the internal iliac artery.…”
Section: Discussionmentioning
confidence: 99%
“…BO (abdominal aorta or IIA) is the only technique that can be employed before CS in patients who need to keep the uterus and reserve fertility. The use of endovascular interventional procedures with BO has been described in the management of obstetric hemorrhage of various causes [24][25] , but the effect of intraoperative IIA BO in women with PPP and PA is still controversial. Some authors advocate the use of IIA BO for treatment of PA, and they found preoperative prophylactic BO was associated with reduced EBL and fewer massive donor transfusions [26] .…”
Section: Discussionmentioning
confidence: 99%
“…[8] In recent years, abdominal aortic balloon, as a new technology, has become more and more popular in women with placenta increta or percreta. [9,10] To evaluate the efficacy and safety of this new technology, we collected relevant clinical data, together with previous articles, to make an analysis and summary. we collected data from patients with placenta increta or percreta who were treated in the Sichuan Provincial People's Hospital and make a comparison on blood loss volume blood transfusion volume and hysterectomy rates between AABO group and NO-AABO group.…”
Section: Introductionmentioning
confidence: 99%